Including the Excluded. Hybrid Networks During Covid19: The Case of the Giambellino Lorenteggio Emergency Community Fund in Milan - Ranzini, Alice (PARTECIPAZIONE E CONFLITTO, 2021)
In the city of Milan, the pandemic generated by the spread of Covid-19 in 2020 led to increased inequality between different social groups. This paper reports the case of a neighbourhood community fund promoted by a group of non-profit organisations in one of the poorest areas of the city during the first lockdown (February-June 2020). While providing emergency aid to people who did not access institutional measures during the pandemic, this initiative has also boosted a process of reconfiguring the local network structure, supporting a collective redefinition of the practices and meanings of territorial networking for welfare provision. Referring to direct social action (DSA) theory, the article reflects on the role of community-based DSAs in innovating welfare policies and addressing social and territorial inequalities, looking at network-shaped forms of cooperation among third sector organisations.